Meta-analyses of the effects of high-intensity interval training in elite athletes — part II: relationships between the mean effects on various performance measures - Hans-Peter Wiesinger; Hans-Peter Wiesinger; Hans-Peter Wiesinger; Will G. Hopkins; Nils Haller; Nils Haller; Julia Blumkaitis; Tilmann Strepp; Thomas Leonhard Stöggl; Thomas Leonhard Stöggl (Frontiers in Physiology)
IntroductionOur recent meta-analyses have demonstrated that high-intensity interval training (HIIT) causes a range of mean changes in various measures and predictors of endurance and sprint performance in athletes. Here, we extend the analyses to relationships between mean changes of these measures and consider implications for understanding and improving HIIT that were not apparent in the previous analyses.MethodsThe data were mean changes from HIIT with highly trained endurance and elite other (mainly team sport) athletes in studies where two or more measures or predictors of performance were available. Relationships between changes in pairs of measures were visualized in scatterplots with points identified by aerobic and anaerobic types of HIIT; simple linear relationships were quantified via log-transformation of factor changes with a meta-regression mixed model.ResultsIn endurance athletes, there were positive linear relationships between mean changes in time-trial speed/power (reflecting competition endurance performance) and mean changes in endurance performance predictors [peak speed/power, maximal oxygen uptake (V̇O2max), and aerobic/anaerobic threshold]. There were substantial differences in time-trial speed/power between studies not explained by each predictor. Exercise economy had an unclear relationship with time-trial speed/power but a decisively negative relationship with V̇O2max. In other athletes, repeated-sprint ability had a weak positive relationship with sprint speed/power. The scatter of points in some plots was associated with the type of HIIT.DiscussionDifferences in time-trial performance between studies for a given change in peak speed/power, V̇O2max, or threshold speed/power imply that time trials should be included when assessing effects of HIIT on endurance performance. Relationships between V̇O2max, time-trial speed/power, and exercise economy suggest that combining aerobic and anaerobic types of HIIT could be more effective for endurance performance. Sprints and repeated-sprint ability are important performance measures for team-sport athletes; their poor relationship implies that both should be measured when assessing HIIT.Clinical Trial Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=236384